Idarat Barnamij Ta’lim al-Lughah al-‘Arabiyah fi al-Muassasah al-Dauriyah Markaz al-‘Arabiyah Pare Kediri - Firdaus, Rousul (Al-Wazan: Journal of Arabic Education, 2024)
The background of this research is based on the importance of effective management in Arabic language learning programs, especially in language course institutions that play a significant role in developing Arabic language proficiency in Indonesia. Markaz Arabiyah Pare Kediri is recognized as one of the leading centers for Arabic language learning, but in-depth research on the management of its programs remains limited. Therefore, this study aims to analyze and evaluate the management of the Arabic language learning program at Markaz Arabiyah, focusing on effectiveness, curriculum relevance, and innovation in teaching methods. The research method used is a qualitative approach with a case study design. Data was collected through in-depth interviews with administrators, teachers, and students, as well as direct observation and document analysis related to program management. The data analysis techniques include data reduction, data display, and conclusion drawing/verification. The objective of this research is to understand the management of the Arabic language learning program at Markaz Arabiyah, including its planning, organizing, implementation, supervision, and evaluation. The research results indicate that the program management at Markaz Arabiyah Pare has successfully created a conducive learning environment that supports the enhancement of students' Arabic language proficiency. However, some aspects need improvement, such as aligning the curriculum with global needs and enhancing the quality of teacher training.